Dierlijke elementen in jeugdige ouderdomsbeeldvorming - Diesfeldt, Han F. A. (Tijdschrift voor Gerontologie en Geriatrie, 2017)
bespreking: Valérian Boudjemadi, Stéphanie Demoulin & Jennifer Bastart (2017). Animalistic dehumanization of older people by younger ones: variations of humanness perceptions as a function of a target’s age. Psychology and Aging, 32: 293–306.